A forma CÊ e a noção de gramaticalização (Revista de Estudos da Linguagem, 1996)
The aim of this paper is to provide an analysis for the complementary distribution between the Brazilian forms você and cê (Uyou"). I argue that cê is a clitic and constitutes a step in the grammaticalization process of the form Vossa Mercê.